INDONESIA-INDIA COOPERATION THROUGH COMPREHENSIVE STRATEGIC PARTNERSHIP (CSP) IN THE FIELD OF DEFENSE AND SECURITY 2018-2022 - Syakbani, Ing Syakbani; Olivia, Yessi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research examines the forms of defense and security cooperation between Indonesia and India in the status of the Comprehensive Strategic Partnership relationship in the range of 2018 to 2022. Indonesia and India agreed on a Defense Cooperation Agreement (DCA) in 2001 and became strategic partners through the Joint Declaration on Establishing a Strategic Partnership in 2005. In its development, Indonesia and India upgraded the status of the partnership between the two countries to become a Comprehensive Strategic Partnership in 2018. This study wants to see how Indonesia-India cooperation in the field of defense and security takes place through the Comprehensive Strategic Partnership. This research uses a qualitative method. Sources come from books, journals, official documents and official pages from the Indonesian Ministry of Foreign Affairs, Indian Ministry of External Affairs, Indonesian Ministry of Defense, Indian Ministry of Defense, which are used to analyze defense and security cooperation between Indonesia and India. The perspective used in this study is neoliberalism, and uses the theory of international cooperation. The results of this study indicated that the forms of defense and security cooperation between Indonesia and India in the Comprehensive Strategic Partnership relationship include Joint Defense Cooperation Committee (JDCC), Defense Ministers' Dialogue, India-Indonesia Security Dialogue (IISD), Joint Military Exercise, Coordinated Patrol (CORPAT), cooperation in Defence Industry, and also cooperation in maritime field between BAKAMLA Indonesia and Indian Coast Guard. In line with the theory used, the two countries cooperate in order to get absolute benefits to achieve national interests and maintain the stability of the security of their respective countries. Keywords: Bilateral Relation, International Cooperation, Defense and Security, Indonesia-India Comprehensive Strategic Partnership.